“Mobile Banking Adoption and Financial Inclusion at the Bottom of the Pyramid: A Theoretical Framework integrating Accounting Accountability, Regulatory, Ethical, and Behavioral Perspectives” (The Journal of Theoretical Accounting Research, 2026)
Mobile banking has become an essential tool to enhance access to financial services, particularly for those who lack traditional banking options. The data was collected from 108 street vendors from selected regions of Northern India, using a snow ball sampling method. This study creates a framework that combines user behavior, regulatory factors, and ethical considerations to understand how mobile banking encourages responsible financial practices. The research expands on existing models to highlight mobile banking's role in fostering ethical and transparent financial actions, beyond just being a tech innovation. The current study strengthens the understanding of how inclusion supported by digital technology can strengthen the ethics, accountability and integrity in financial reporting and governance systems through integration of digital adoption with accounting theory. The model prioritizes theoretical framework integration over empirical applicability, providing a framework for upcoming research on the behavioral and ethical foundations of accounting in the domain of digital finance.